IMPLEMENTATION OF PROJECT BASED LEARNING IN THE COMPILATION OF STUDENTS' SCIENTIFIC ARTICLES: A CASE STUDY - Reri Seprina Anggraini; Aan Putra; Maila Sari (Irfani, 2024)
The ability to write scientific articles is an essential competence for university students, yet many still encounter difficulties due to limited research experience and theory-oriented instructional approaches. This study aims to examine the implementation of Project-Based Learning (PjBL) in the Research and Scientific Publication course and its role in facilitating the production of students’ scientific articles. Using a qualitative case study design, the research involved 17 sixth-semester students of the Mathematics Education Department at the State Islamic Institute (IAIN) Kerinci. Data were collected through classroom observations, in-depth interviews, and documentation of students’ scientific articles, and analyzed using an interactive model of data reduction, data display, and conclusion drawing. The findings indicate that PjBL was generally implemented effectively, particularly in the stages of problem orientation and article writing, while project planning, data collection, and reflection were implemented at a moderate level. Most students perceived PjBL as a meaningful and authentic learning experience that enhanced their understanding of research processes and scientific article structure. Furthermore, the majority of students were able to produce complete IMRaD-structured articles with adequate to good quality. These results suggest that PjBL is a promising instructional approach for improving students’ scientific writing skills in higher education